Applications-Based Learning Media to Improve Students’ Table Tennis Basic Skills: Viewing its Effectiveness - Samsuddin Siregar; Eva Faridah; Rosmaini Hasibuan (STAI Hubbulwathan Duri, 2023)
This study aims to test the effectiveness of application-based learning media in improving basic table tennis technical skills. The sample in this study involved students consisting of two groups, namely the experimental group of 15 people and the control group of 15 people. The research was carried out online, and this was because it was still in an emergency due to the Covid-19 pandemic. The method used in this study is an experimental method to see the difference in skill levels of the two research groups. The data collection technique used is performance tests. Then the data were analyzed by calculating the percentage. The results of data analysis obtained through skill performance tests show that the level of basic table tennis technical skills in the experimental group and the control group both have good results. However, looking at the comparison of the percentage levels obtained by the two groups, it can be seen that the experimental group has a higher skill level percentage than the control group. An experimental group is a group whose learning activities use application-based learning media. Based on the research results above, it can be concluded that online learning using application-based media can improve students’ understanding and skills in basic table tennis technical material.